"All of a sudden, a lot less still makes it worthwhile to be alive:" Palliative care patients' views on life. Issue 2 (8th March 2018) - Romotzky, Vanessa; Strupp, Julia; Hayn, Alexander; Rüffer, Jens Ulrich; Grümmer, Judith; Voltz, Raymond
Abstract: Objective: We aimed to elucidate the views on life as narrated by patients in palliative care (PC) to find out what patients deem to be essential in their life, whether something has changed concerning their view of life in light of the disease, and whether interviewees would like to give others something to take with them. Method: Data were collected from narrative audio and video interviews with 18 inpatients in a specialized PC unit. Interviews were recorded and transcribed verbatim and analyzed using qualitative content analysis applying MAXQDA software. CDs and DVDs with recorded interviews were provided to patients. Result: Eighteen interviews were analyzed: 11 audio and 7 video recordings. The age range was 41–80 years. Patients reported on changes in their views on life. Despite it being a complex and painful process, patients still gave examples of benefits experienced during their illness trajectory. Patients identified resources and coping strategies such as meaningful contacts with close others and mindfulness. Shifts have occurred in terms of taking more time for themselves, enjoying the moment, being more calm, and spending more time with family and friends. What patients wanted to pass on to others was to pay attention to the needs of both the self and the others, shape your life individually, confront yourself early with issues of death and dying, and care for your fellow human beings. Patients and relatives valued the opportunity to keep their interview as a CD/DVD. Significance of results: Results support the idea that many people facing terminal illness continue to focus on living and remain within their biographies and the contexts of their lives, even if their functional status declines. Patients and relatives appreciated that interviews were provided as kind of a legacy. Yet, more robust research is needed to decide whether such interviews yield any therapeutic effect.